Pengaruh Financial Distress, Pertumbuhan Perusahaan dan Pergantian Manajemen Terhadap Auditor Switching - Ismyatun Mahdatila; Endang Kartini; Rusdi Rusdi; Ida Ayu Nursanty (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this research is to analyse the effect of financial distress, company growth and management turnover of the switching auditor at open manufacturing companies listed on the BEI year 2016-2020. So that this research variable consists of 4 (four) variables, the independent variable is financial distress (X1), company growth (X2) and management turnover (X3) and auditor switching as the dependent variable (Y). Population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period, totaling 193 companies. Data obtained the processed by using logistic regression analysis method. The criteria are based on (1) companies that are included in manufacturing companies listed on the Indonesia Stock Exchange 2016-2020; (2) companies that issue financial statements consecutively from the 2016-2020 period; (3) companies that perform auditor switching during the 2016-2020 period. Of the 193 listed companies there are 35 companies that meet the sample criteria with a study period of 5 years, so the number of sample observations used is 175. The data were obtaine using documentation tehniques in the form of financial statements of manufacturing companies for 2016-2020. The test results of this tudy indicate that the variables of financial distress, company growth and management turnover do not ave a positive effect on auditor switching.